Energy balance during disruptions. (12th August 2020) - Isernia, N; Scalera, V; Serpico, C; Villone, F
Abstract: In the operation of tokamaks, hard-to-predict fast transient events, called disruptions, are often responsible for severe energy deposition on the structures surrounding the plasma. In this paper, first of all we derive an overall energy balance for a disruptive plasma, then we use an evolutionary equilibrium code (CarMa0NL) to reproduce the macroscopic plasma evolution during a disruption of a sample high-aspect-ratio circular plasma, analysing the energy fluxes which take place during the event. We show that the variations of toroidal magnetic energy are compensated by one portion of the Poynting vector flux, and that dissipated heat during the Thermal Quench is mainly related to the loss of internal energy. Moreover, we develop an analytical model providing physical insight on the energy deposition on the wall during the Current Quench, related to the poloidal magnetic energy, in a quantity depending on the time scale of the event compared to the electromagnetic time constants.